Evaluation of the anti-nociceptive effects of morphine, tramadol, meloxicam and their combinations using the tail-flick test in rats - Foroud, Mehrzad (Vet Res Forum, 2015)
The purpose of the present study was to evaluate anti-nociceptive effects of morphine, tramadol, meloxicam and their combinations in rats. Seventy male Wistar rats were divided into seven equal groups and randomly assigned to receive intraperitoneal saline (S) (control group, 1.0 mL kg(-1)), morphine (MO) (4.0 mg kg(-1)), tramadol (TR) (12.5 mg kg(-1)), meloxicam (ML) (1.0 mg kg(-1)), tramadol- morphine (TR-MO), meloxicam-morphine (ML-MO) and meloxicam-tramadol (ML-TR) at the same doses. Anti-nociception was evaluated using tail flick latency (TFL) test at 45, 60, 75, 90 and 120 min after drug injection. The TFL was significantly higher in TR and MO groups compared to S group for 90 and 120 min, respectively. No significant change in TFL from baseline values was observed at all time points in ML group. Among rats that received combination of analgesics, those that received TR-MO had significantly greater TFL. There was no significant difference in TFL between ML-TR and ML-MO groups. In conclusion, TR, MO and their combination all provided acceptable anti-nociceptive effects in rats. Meloxicam at the given dosage (1.0 mg kg(-1)) did not demonstrate any anti-nociceptive effect when evaluated by TFL test.